The Effect of Guided Questions and Students’ Motivation towards Writing Ability - Septaniar Septaniar (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2017)
The objectives of this study were to find whether: (1) there is significant difference inwriting achievement between the students who are taught using guided questionstechnique and conventional method; (2) there is significant difference in average scorebetween high motivated students and low motivated students who are taught usingguided questions and conventional method; (3) and there is an interaction effect oftechniques and students’ motivation in writing ability. This research was conducted atSMPN 1 Sekayu. Sample of this research was 70 students of the eighth grade students(35 students were as experimental group and 35 students were as control group). Themethod of the research was a factorial design. The data were collected through the testand questionnaire and were analyzed by using independent sample t-test and two-wayANOVA. The finding showed that: (1) there was significant difference in writingachievement between the students taught using guided questions; (2) there wassignificant difference between in average score between high motivated students taughtusing guided questions and conventional method; (3) there was no significant differencein average score between low motivated students taught using guided questions andconventional method; (4) there was no significant difference between high and lowmotivated students who taught using guided questions; (5) there was no significantdifference in average score between high motivated students and low motivated studentstaught using conventional method; (6) and there was no an interaction effect oftechniques and students’ motivation in writing ability.